2012
DOI: 10.2340/00015555-1301
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pyoderma Gangrenosum: Successful Resolution with Infliximab Therapy and Pro-inflammatory Cytokines Assessment

Abstract: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis\ud of unknown aetiology, characterized by primarily\ud sterile, painful ulcers with typical violaceous undermined\ud borders and mucopurulent or haemorrhagic exudate. PG is\ud commonly associated with other systemic disorders. Diagnosis\ud of primary idiopathic forms is reached following the\ud exclusion of inflammatory bowel disease (IBD), rheumatic\ud disorders, monoclonal gammopathy and solid tumours\ud (1, 2). Treatment is generally based on corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 3212 unique citations were found. 1286 and 1704 citations were excluded by abstract and full‐text read, respectively, yielding 222 articles…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3212 unique citations were found. 1286 and 1704 citations were excluded by abstract and full‐text read, respectively, yielding 222 articles…”
Section: Resultsmentioning
confidence: 99%
“…IL‐8 (also known as CXCL8) 13,15–19 and TNF‐a 13,15,16,18–23 were consistently found to be overexpressed in the wound bed of PG lesions, with the latter also being elevated in the serum of PG patients (Table 2). IL‐8 is a potent chemoattractant for neutrophils and, along with inflammatory effects of TNF‐a, may contribute to an ongoing neutrophil presence in PG tissue.…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐a antagonism through infliximab or etanercept has also proven effective, although the time to complete resolution appears longer when compared to IL‐23 or IL‐17R inhibition, with complete healing occurring by 12 months 23,44 . A larger study examining adalimumab in 22 patients with PG demonstrated an average change of ulcer size of −63.8% from baseline to week 26, and a mean target healing time of 114.9 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our treatment experience points to infliximab, adalimumab as the most valuable remedies for this disease. Inflixi- mab has been previously described for idiosyncratic PG (14). Any effect of high-dose IVIG therapy (15) was unnoticeable in our patient after 6 weeks.…”
Section: Discussionmentioning
confidence: 80%